Study of Treatment Modalities for Blunt Abdominal Trauma and its Medicolegal Aspect - Keyur N. Surati; Jainam Shah; Rohit Zariwala; Yogesh Modiya; Jatin Modi; Ronak Modi (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Blunt abdominal trauma management has changed drastically from surgical to conservative. In ourstudy we analyzed 100 patients visited hospital with blunt abdominal trauma and diagnostic and managementmodalities and medicolegal aspect are discussed.Study evaluate the incidence and clinical presentation, various available investigations, the organs affected inblunt abdominal trauma and management of complications, morbidity and mortality following blunt abdominalinjury.To handle such cases to save the patient and our self from litigation.Material and methods: This study consists an analysis of randomly selected 100 cases with blunt abdominaltrauma admitted during the period of May 2018 to August 2020. It is a prospective observational study.Conclusion: Blunt abdominal trauma is on rise due to excessive use of motor vehicles. From our study weconcluded that single solid organ injury patients with hemodynamic stability (specially Grade 1 to grade 3)managed conservatively more compared to multiple solid organ injury patients and best investigated by USGFAST and CT scan.Careful record keeping can assist to protect against bogus and false allegations and complaints,as in court of law documentation is considered as part of witness.